Våtoxidation av svartlut med syre för avskiljning av koldioxid - Gunnarsson, Johan; Sundborg, Oskar; Scott, Ellen; Bengtsson, Mathias; Bergqvist, Daniel; Arvidsson, Pontus (My University, 2016)
One of the greatest challenges of our time in an environmental point of view is greenhouse gas emissions and specially carbon dioxide emissions. Higher levels of greenhouse gas in the atmosphere leads to a raise of the average temperature on earth, which results in disasters such as drought, storms and flooding. Carbon capture and storage is therefore a necessary technology to develop, especially for fossil fuels but also for biomass. With carbon capture and storage from fossil fuels the emissions can at the very best be reduced to zero but it is not possible to remove carbon dioxide from the atmosphere, this is made possible by using biomass combined with storage. In order to achieve so called negative emission levels, which results in lower greenhouse gas levels in the atmosphere, it is necessary to implement new technologies. There are currently a few proposed technologies for carbon capture and storage and this report aims to study a new process technique, wet oxidation with oxygen, which is intended to be implemented in the pulp- and paper industry to make carbon capture and storage possible for the carbon dioxide produced by oxidation of black liquor. The process is intended to replace the recovery boiler and the evaporator and since two major process units are replaced this can enable economic savings and significant emission reductions. A modelling of a reactor was included in the project and it shows that by replacing air with oxygen a higher temperature can be achieved in the reactor. Furthermore, the degree of conversion is higher when using oxygen, partly because of the higher temperature but also because of a higher concentration of oxygen in the reactor. The process optimization shows that the process is self-sufficient and that excess process steam can be exported. The results show that about 400 million SEK can be saved using a process with a capacity of 35.275 kg/s compared with investing in a new recovery boiler with carbon capture and storage, and that the designed process can capture about 0.27 million tons’ carbon dioxide/year. The degree of separation for the process with respect to carbon dioxide was 88.6 mole % and the conversion with respect to the organic fraction in the black liquor was over 98 %.
Keywords: Energi; Energiteknik; Energy; Energy Engineering